Zinc as nutritional intervention and prevention measure for COVID–19 disease. Issue 1 (17th June 2020) - Mossink, J P
Abstract : The present spread of severe acute respiratory syndrome coronavirus 2, provoking COVID–19 disease, progresses rapidly worldwide. In current absence of a curative treatment and an effective, safe vaccine, there is a pressing need to focus on identifying and correcting deficits in immune function in order to reduce risk of severe progress of the disease and to lower the number of infections and fatalities. This paper evaluates the most recent literature on zinc status related to antiviral immunity and its possible role in COVID–19. It is concluded that zinc is a critical factor for antiviral immunity. There is ample evidence suggesting that zinc depletion, also prevalent in high–income nations, compromises immune functions. Notably, major risk groups for COVID–19, the elderly, men more than women, obese individuals and patients with diabetes are all at risk of zinc deficiency. Moreover, various widely used antihypertensive drugs and statin therapy have been reported to negatively influence zinc status. As zinc depletion impairs antiviral immunity, it is hypothesised to increase susceptibility for COVID–19. Therefore, dietary preventive measures and prompt implementation of zinc supplementation for risk groups should be considered. Large–scale studies are urgently needed to investigate the role of micronutrients and antiviral immunity, in particular drug–micronutrient immunity interaction.